2019
DOI: 10.1101/726653
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resilience to multiple stressors in an aquatic plant and its microbiome

Abstract: 1Premise Environments are changing rapidly, and outcomes of species interactions, es-2 pecially mutualisms, are notoriously dependent on the environment. A growing number 3 of studies have investigated responses of mutualisms to anthropogenic changes, yet most 4 studies have focused on nutrient pollution or climate change, and tested single stres-5 sors. Relatively little is known about impacts of simultaneous chemical contaminants, 6 which may di↵er fundamentally from nutrient or climate stressors, and are… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 83 publications
(114 reference statements)
0
14
0
Order By: Relevance
“…In the wild, the fronds and roots are covered in a species rich assemblage of microbes (Gilbert et al 2018, Acosta et al 2020, which can be removed by sterilisation in the lab when used as an experimental model (Bowker et al 1980). Interest in the L. minor microbiome dates back to the early 20 th C, with the observation of an association with N-fixing bacteria (Bottomley 1920), and has accelerated in recent years (Ishizawa et al 2017a, 2017b, 2019, Gilbert et al 2018, Chen et al 2019, Acosta et al 2020, Iwashita et al 2020, O'Brien et al 2020a, 2020b, Tan et al 2021 with a general consensus that plant-microbe interactions play an important role in mediating plant fitness and function. Although most of this research focuses on identifying specific PGPB strains, recent work has characterised the complete core bacterial assemblage associated with L. minor (Acosta et al 2020), which consists of largely Proteobacteria (Pseudomonas and Actinobacteria) and bears a close resemblance to the leaf microbiome in terrestrial plants like Arabidopsis and rice.…”
Section: Introductionmentioning
confidence: 99%
“…In the wild, the fronds and roots are covered in a species rich assemblage of microbes (Gilbert et al 2018, Acosta et al 2020, which can be removed by sterilisation in the lab when used as an experimental model (Bowker et al 1980). Interest in the L. minor microbiome dates back to the early 20 th C, with the observation of an association with N-fixing bacteria (Bottomley 1920), and has accelerated in recent years (Ishizawa et al 2017a, 2017b, 2019, Gilbert et al 2018, Chen et al 2019, Acosta et al 2020, Iwashita et al 2020, O'Brien et al 2020a, 2020b, Tan et al 2021 with a general consensus that plant-microbe interactions play an important role in mediating plant fitness and function. Although most of this research focuses on identifying specific PGPB strains, recent work has characterised the complete core bacterial assemblage associated with L. minor (Acosta et al 2020), which consists of largely Proteobacteria (Pseudomonas and Actinobacteria) and bears a close resemblance to the leaf microbiome in terrestrial plants like Arabidopsis and rice.…”
Section: Introductionmentioning
confidence: 99%
“…I added NaCl (Sigma-Aldrich, 99.5% purity) to half of the tubs (17.53 +/-0.01 g / 6L) for a final concentration of 50 mM. This salt concentration has been shown to be harmful but not lethal to L. minor (Sree et al 2015;O'Brien et al 2020). The salt was added to pre-labelled replicates 3 and 4 for all experimental cultures.…”
Section: Glasshouse Experimentsmentioning
confidence: 99%
“…In polycultures, ecotypes under attack by such algae could have experienced a reduction in pathogenic load because of a host-dilution effect, similarly to the positive effect of plant species richness on soil pathogens (Schnitzer et al 2011;Maron et al 2011). Interestingly, it has previously been found that L. minor associates with a diverse and mostly beneficial microbial community (Ishizawa et al 2017;O'Brien et al 2020). However, the placing of the L. minor populations in tap water under greenhouse conditions may have selected for a subset of algae, which were on average growth-inhibiting.…”
Section: Effects Of Intraspecific Diversity On Whole-population Abundancementioning
confidence: 99%
See 1 more Smart Citation
“…O'Brien et al. () investigated the impacts of common city stream contaminants—sodium chloride (salt) and benzotriazole (a common corrosion inhibitor)—on interactions between the duckweed Lemna minor and its microbiome. While they found that salt decreases both plant and microbial growth, benzotriazole provided a slight benefit to plant growth, but only when salt and microbes were absent.…”
Section: Living Togethermentioning
confidence: 99%